Упростите выражения.

0 голосов
40 просмотров

Упростите выражения.


image

Алгебра (1.2k баллов) | 40 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

A)   ..............= \frac{(2x+1)(1-2x)-1}{1-2x} : \frac{2x(2x-1)-4 x^{2} }{2x-1}= \frac{1-4 x^{2} }{-(2x-1)}* \frac{2x-1}{4 x^{2} -2x-4 x^{2} }=\frac{1-4 x^{2} }{2x}

.б)................
=(\frac{pq}{(p-q)(p+q)}- \frac{q}{p-q}): \frac{(p-q)(p+q)+4q^{2} -p^{2} }{p+q} =\\ \\ \frac{pq-q(p+q)}{(p-q)(p+q)} * \frac{p+q}{p^{2} - q^{2}+4q^{2} - p^{2} } = \frac{- q^{2} }{3 q^{2}(p-q) } =- \frac{1}{3(p-q)} = \frac{1}{3(q-p)}

(322k баллов)